Reframing social mix in affordable housing initiatives in Italy and in the Netherlands. Closing the gap between discourses and practices?. (July 2019) - Costarelli, Igor; Kleinhans, Reinout; Mugnano, Silvia
Abstract: European countries are facing rising demand for affordable housing by a widespread and differentiated audience. Both in Italy and in the Netherlands policy-makers and practitioners address this emerging need by implementing new social housing projects targeting diverse social groups – such as students, young households, welfare dependents, and refugees – which results in a fine-grained social mix. This paper discusses the development of these initiatives within wider trends in housing policies and in relation to the domestic debate on social mix in the two countries. Drawing on Magic Mix and Housing Sociale projects as case studies, respectively in the Netherlands and in Italy, we aim to explore and unfold the contemporary meanings and the practices attached to the idea of social mix. In so doing, this paper paves the way for a new conceptualization of social mix in the current post-crisis and hyper-diversified European scenario. We discuss traces of continuity and discontinuity between these forms of social mix and the mainstream idea of tenure mix, which has been a cornerstone of area-based urban renewal policy in many European countries. This paper contributes to the existing literature by offering insights into new practices of social mix in housing sphere. Highlights: Societal and historical contexts influence policy approaches, discourses, and values attached to the idea of social mix. Recent forms of social mix in social housing projects in Italy and the Netherlands target a variety of low-income groups. Social mix is reframed along five domains: discourses, target groups, practices, institutional frame, urban downscaling. New role models are defined according to tenants' resourcefulness, rather than economic capital (i.e. middle-classes). Mechanisms of conditionality require tenants to take part in community-oriented activities in return to affordable rents.